Years of potential life lost in HIV/AIDS patients and its determinant factor (Research, Society and Development, 2020)
Padang is one of the areas in West Sumatera with the highest HIV/AIDS cases. There are 370 HIV cases and 39 AIDS cases in 2017. These cases increased in 2018 to 447 cases for HIV and 103 cases for AIDS. This study aimed to find out the description of HIV/AIDS patients who have been passed away due to socio-demography characteristics. Also to know the number of Years of Potential Life Lost (YPLL) caused by HIV/AIDS infection and its determinant factors. This study used a quantitative methodology with retrospective cohort study design and collected the data from medical records installation in RSUP Dr. M. Djamil Padang on patients with HIV/AIDS diagnosis that have been passed away. The data then analyzed using independent t-test, one-way ANOVA, and multiple linear regression. The result showed that 186 of death cases happened on 2015-2020 were mostly dominated by man (76.34%) with the average age around 31 years old, married (65.59%), and infected through heterosexual relationship (29.03%). The average year of YPLL was 26.09 year. Moreover, this study found that there was a significant relation between ARV therapy (CI 95% P= 0.002) and the total of CD4 diagnosed with YPLL (CI 95% P= 0.0001). Therefore, respondents of productive age should get serious attention from the Government and society around. Also for the Health Office and AIDS prevention commission were expected to make innovations in preventive promotive efforts and strengthening surveillance system on HIV/AIDS either to the risky group or general society.